2018
DOI: 10.1108/jepp-d-18-00033
|View full text |Cite
|
Sign up to set email alerts
|

Targeted state economic development incentives and entrepreneurship

Abstract: Purpose The purpose of this paper is to examine the relationship between state economic development incentives programs and entrepreneurial activity. Design/methodology/approach The authors use panel data and a fixed-effects model to examine the determinants of five measures of entrepreneurial activity. To measure state economic development incentives programs, they use a new and substantially improved data set from Bartik (2017). They also include a measure for economic freedom, the Fraser Institute’s Econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The spiritual and material incentives enhance extrinsic and intrinsic motivations and green creativity (Liu and Liu, 2023). On the other hand, Tuszynski and Stansel's (2018) findings underline that in terms of SMEs, there is a negative association between incentives and patent activity and small business establishments. From employing the AMO theory, Mia et al (2022) claim that incentives, entrepreneurship education and skills have a positive and significant influence in promoting GE.…”
Section: Green Incentives (Gis) and Green Entrepreneurship (Ge)mentioning
confidence: 89%
“…The spiritual and material incentives enhance extrinsic and intrinsic motivations and green creativity (Liu and Liu, 2023). On the other hand, Tuszynski and Stansel's (2018) findings underline that in terms of SMEs, there is a negative association between incentives and patent activity and small business establishments. From employing the AMO theory, Mia et al (2022) claim that incentives, entrepreneurship education and skills have a positive and significant influence in promoting GE.…”
Section: Green Incentives (Gis) and Green Entrepreneurship (Ge)mentioning
confidence: 89%
“…Bruce and Deskins (2012) used counts of tax and nontax incentives in a panel framework and found a small positive relationship between tax incentives and their measures of entrepreneurial activity and a small, negative relationship between nontax incentives and sole proprietorships. Using a state-level version of the data used in this article, Tuszynski and Stansel (2018) found that incentives are negatively related to patents and small business establishments, are positively related to large business establishments, and have no significant relationship with new business formation or sole proprietorships. These two studies represent the most recent and comprehensive evidence regarding start-ups and economic development incentives.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Traditional theories of public administration and regulation see government agencies playing a primary role in institutions. This continues at the national level; however, recent studies highlight institutional elements separate from government, especially in the context of entrepreneurship (da Cunha and Arvate, 2021; Tuszynski and Stansel, 2018; Urban and Dlamini, 2020) and regional and local economic development, where government agencies participate within and facilitate economic and entrepreneurial ecosystems alongside other actors (Bramwell et al. , 2019; Jolley and Pittaway, 2019; von Bloh, 2021; Walsh, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%